RANCANG BANGUN INSINERATOR DUA TAHAP (SOLUSI MENGATASI POLUSI UDARA PADA PEMBAKARAN SAMPAH) - Hermansyah, Hermansyah; Said L., Muh.; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2017)
This study aims to determine the model design and the incinerators tool mechanism to tackle air pollution in burning waste. The filter used is water by spraying using a spray nozzle on the tube filter. Testing is done by testing and observing the work incinerator combustion in incinerators and burning freely. Observations for plastic waste with a mass of 1 kg burned freely color black smoke, combustion rate 2 kg/hours, the combustion efficiency of 67.5 %. Combustion in incinerators two-stage color white smoke, combustion rate of 1.7 kg / h, the combustion efficiency of 67.5 %. At burning incinerator is better than burning freely.Â Keywords: Insinerator, asap, water spray, air